The new world power : American foreign policy, 1898-1917 - Hannigan, Robert E. (University of Pennsylvania Press, 2002)
"Straightforward enough to serve as a useful textbook and thorough enough to engage expert readers ... Intelligent, readable, and thoughtful."--Foreign Affairs.